DEVELOPING AUDIO VISUAL MEDIA BASED ON PROBLEM BASED LEARNING IN ENGLISH LANGUAGE TEACHING - Raya, Valentina Letek; Manurung, Sulastri; Yana, Dewi (English Department, University of Riau Kepulauan, Batam,Indonesia, 2023)
Audio-visual media is an alternative of conducting technology-based learning that can optimize the learning process. This study aims to determine the needs, quality, feasibility and effectiveness of the developed audio-visual media in English Language Teaching (ELT). This study applied the Research and Development of ADDIE (analysis, design, development, implementation and evaluation). The analysis stage was carried out by interviewing English teachers and students’ self- report. The design stage was carried out by planning the systematic, media outline, and evaluation tools. The development stage includes editing and revision. A pre-test was distributed to the students followed by validation by material expert, media expert and learning practitioners. The validated product then was implemented followed by a post-test. Pre-test and post-test data were used to test the media effectiveness through the paired t-test. The findings showed that the developed animated video equipped with manual for teacher was feasible and supported by the result of paired t-test which showed that it was effective for use as a learning media in ELT.